The effect of herbal oil and citric acid on vase life of cut narcissus flower (Narcissus tazetta L.) - GUN, S (Journal of Postharvest Technology, 2020)
The study was conducted to determine the effects of different herbal oils and citric acid on vase life of cut narcissus (Narcissus tazetta L.)  flower. Cut narcissus flowers were placed in 100 ppm dose vase solutions containing lavender, nettle and melissa essential oil and rosin oil  and citric acid. At the end of the study, the longest vase life (9, 8.5 and 8 days) was obtained from citric acid, rosin oil and melissa essential oil  respectively, and other oil applications increased vase life compared to the control as well as. The highest relative fresh weight (116.1, 109.8  and 107.7%) during vase life was obtained from citric acid, melissa and nettle essential oil with respectively. All applications (except nettle  essential oil) were effective in the increasing of the water uptake. As a result, it was determined that lavender, nettle and melissa essential oil  and rosin oil were effective in increasing vase life of cut narcissus flower. In addition, in the study, it is necessary to determine the effects of  nettle essential oil and rosin oil, which have positive effects on vase life, by applying them to vase solution of different cut flowers.
Keywords: Antimicrobial,; essential oil; relative fresh weight,; rosin oil; water uptake